GM-CSF: An immune modulatory cytokine that can suppress autoimmunity. Issue 2 (October 2015) - Bhattacharya, Palash; Thiruppathi, Muthusamy; Elshabrawy, Hatem A.; Alharshawi, Khaled; Kumar, Prabhakaran; Prabhakar, Bellur S.
Highlights GM-CSF is an established growth and differentiation factor for multiple cell lineages. The role of GM-CSF in steady state myelopoiesis appears to be redundant. GM-CSF has an additional role in the modulation of myeloid cell functions. Immune modulatory role of GM-CSF determines the outcome of many autoimmune diseases. We review literature to discuss of the role of GM-CSF in immune tolerance.